TENSILE MEMBRANE STRUCTURE AS A FILLING STATION ROOF IN BANGLADESH, A PRACTICAL PROJECT, METHODOLOGY AND DESIGN PROCESS - Sultana, Latifa (International Journal of Psychosocial Rehabilitation, 2020)
Tensile Membrane Structure may be an innovative alternate solution for Filling Station Roof in Bangladesh. Most of the filling station in Bangladesh are constructed developing low land adjacent to the highway and most of the roofs are constructed by R.C.C. Roofs height are generally more than 5.5 meter. In Bangladesh these height are not conventional for other typical building. So shuttering materials specially props for this height are not available. There is happened many accident during construction of this roof for heavy selfweight of R.C.C and lacking of proper shuttering and improper soil improvement.Tensile Membrane Structure is a very light weight structure. So foundation costing is very much economical than other conventional structure. No shuttering materials are required. Chances of accident during construction are reduced. So it is safe for construction. This light weight structure allows to freely innovating exciting solutions for the buildings which may attract general people including customer and make a better business opportunity. So Tensile Membrane Structure may be the best solutions for this type of project in Bangladesh.